Perancangan Sistem Informasi Eksekutif Penggajian Karyawan Pada Galon Air Fino Water - Giska Melvy Anggraini; Maya Ardila Pasaribu; Nur Annisa; Harahap, Solly Rahman Nur; Zuhra Sartika; Fitriana Harahap; Husin Sariangsah (Jurnal Sistem Informasi dan Ilmu Komputer, 2023)
Executive Information Systems (ISE) have become an integral part of modern corporate management, providing executives with relevant and immediate information to support decision making. This journal discusses the implementation of the Executive Information System in the employee payroll process using the Microsoft Visual Studio 2010 development environment and SQL Server database. This research includes the design, development and implementation of an Executive Information System application for the employee payroll department. The system development methodology focuses on requirements analysis, application design, coding, testing, and implementation. Microsoft Visual Studio 2010 is used as the primary development environment, providing powerful tools for building intuitive and efficient user interfaces. SQL Server database is used as an integrated and secure data storage. This application is designed to manage payroll information, including employee personal data, salary history, salary deductions and bonuses. The advantages of this system include the ability to provide real-time information to executives, increase the efficiency of human resource management, and support faster and more accurate decision making in the context of employee payroll.